KAJIAN CEMARAN MIKROBIOLOGIS CILOK DAN SAUS KACANG DI KOTA SURAKARTA - Eko Yuliastuti; Nanik Suhartatik; Akhmad Mustofa; Desy Lustiyani; Nanda Pratiwi (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Cilok was a traditional food originating from Bandung and comes from the abbreviation of